Effect of temperature on the corrosion behavior of 13Cr stainless steel under a high CO2 partial pressure environment - LI Da-peng; ZHANG Lei; SHI Feng-xian; WANG Zhu; LI Hui; LU Min-xu (工程科学学报)
This article is focused on the effect of temperature on the corrosion electrochemical behavior of 13Cr martensitic stainless steel under a high temperature and high CO2 partial pressure environment. Cyclic polarization(CP) measurements,electrochemical impedance spectroscopy(EIS),Mott-Schottky plot measurements,ZSIMPWIN software,and scanning electron microscopy(SEM) are used in this study. The results show that the stability of passive films formed on the 13Cr stainless steel surface decreases with increasing temperature under a high temperature and high CO2 partial pressure environment. This leads to increases in the corrosion rate and pitting susceptibility.